WAHYU 20:1-10 DAN MILENIALISME: SEBUAH EVALUASI HERMENEUTIS DAN KANONIKAL - Nggadas, Deky Hidnas Yan (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2023)
Revelation 20:1-10 is the only text that explicitly speaks of The Millennial Kingdom but has given rise to three main Millennial views: Premillennialism, Postmillennialism, and Amillennialism. This paper intends to carry out a critical evaluation of these three views. The method used is a literature study with a descriptive-evaluative approach from a hermeneutical and canonical perspective. It can be concluded that the Amillennialism view is more persuasive to adhere to, although it is not without difficulties.